Meningkatkan Kepuasan Menginap Melalui Peningkatan Kualitas Pelayanan dan Fasilitas Hotel - I Komang Nataliana; Kadek Feni Aryati; I Gusti Ayu Eka Suwintari; A.A.A Arun Suwi Arianty (Abdimas Indonesian Journal, 2026)
Guest satisfaction is a crucial factor influencing the success of the hospitality industry, as it is closely associated with customer loyalty, hotel reputation, and business competitiveness. Based on observations, discussions with the management, and an analysis of guest reviews on the Booking.com platform, D’Nusa Beach Club and Resort continues to face challenges related to service quality and hotel facilities. These challenges include suboptimal service delivery, ineffective complaint handling, inconsistent room cleanliness, and several facilities requiring maintenance. This community service program aimed to improve service quality and facility management to enhance guest satisfaction. The methods employed included problem identification, socialization, service excellence training, facility management assistance, and evaluation. The socialization and training focused on service excellence, effective communication, customer experience, and complaint handling. Assistance activities included strengthening housekeeping standards, developing housekeeping checklists, and providing recommendations for regular facility maintenance. The results indicated an improvement in participants' understanding of the importance of responsive, friendly, and professional service, as well as increased awareness of the significance of facility maintenance and cleanliness standards in supporting guest comfort. Furthermore, the hotel management demonstrated a commitment to implementing the recommended improvements to enhance service quality and hotel facilities. This program contributed positively to strengthening human resource capacity and facility management, thereby supporting the continuous improvement of the guest experience.